Interconnecting outriggers system in tall building structure - Nasr, Ali Hadian (2014)
Tall building are innovative structure that shall be studies their systems and connections to accept stability in related to certain lateral load such as seismic loads post-earthquake and wind loads. Central core are a major structural element that designed in combination to frames which interact through outriggers to transfer the loads to the foundation. The issue of rigidity is the cooperation between elements in tall building systems. Significantly, type of connections among components based on their stiffness can be defined in the form of percentage of safe distribution of loads in tall building system. The research proposes a design of interconnecting of tall building blocks distribution through tensile force and The effect of soil pressure at underground levels that creates a lateral forces that push the face of the frames below ground level is also another form of loads. In summary, this research is to understand the effect of interconnecting of blocks on overall formation stiffness based on different analysis Models. It figures out the effect of inter connecting at abutment in levels on retaining wall and self -stability of frame related to soil pressure.